Synthesis and characterization of nylon 6 polymer nanocomposite using organically modified Indian bentonite - Kumaresan, S.; Rokade, Dhammaraj S.; Marathe, Yogesh N.; Ingole, Pravin G.; Pawar, Radheshyam R.; Pol, Harshawardhan V.; Bajaj, Hari C. (SN Applied Sciences, 2020)
In this present research work two different organic compounds are applied for the modification of Indian origin bentonite. One is with n-hexadecyltrimethylammonium bromide (CTAB), intercalated with an interlayer of bentonite via cation exchange mechanism. Whereas, another with 3-Aminopropyl trimethoxysilane (APTES) interlayer functionalization with bentonite –OH group. APTES and CTAB–intercalated bentonites samples were further cross modified with CTAB and APTES to obtain novel co-surfactant locked organo bentonite modeling (CLOM) like matrices. Original and modified bentonite samples were comparatively evaluated by advanced characterization techniques such as, powder X-ray diffraction, Fourier-transform infrared spectroscopy, thermal gravimetric analysis (TGA). Moreover, the applicability of the developed CLOM like materials were investigated in nylon 6 nanocomposite preparation by melt compounding method using a micro twin co-rotated extruder. Additionally, CLOM-nylon-6 polymer nanocomposites were characterized by wide angle X-ray diffraction, TGA, differential scanning calorimetry, atomic force microscopy and tensile strength measurement. The observed thermograph results confirmed no significant difference in the thermal properties of the developed composites. Whereas, the significant variation observed in the tensile strength results particularly for developed composite 5% of N6-OAMSB and N6 AMOSB 5 showed 111.5 and 76.6% respective enhancement in tensile strength results when compared with a bare nylon-6 polymer.